Advanced composites for hard‐tissue engineering based on PCL/organic–inorganic hybrid fillers: From the design of 2D substrates to 3D rapid prototyped scaffolds. Issue 9 (18th April 2013) - De, R.; Gloria, A.; Russo, T.; D'Amora, U.; D'Antò, V.; Bollino, F.; Catauro, M.; Mollica, F.; Rengo, S.; Ambrosio, L.
<x xml:space="preserve">Abstract</x> The bioactivity of sol–gel synthesized poly(ε‐caprolactone) (PCL)/TiO2 or poly(ε‐caprolactone)/ZrO2 particles was already known. In designing innovative 2D composite substrates for hard‐tissue engineering, the possibility to embed PCL/TiO2 or PCL/ZrO2 hybrid fillers into a PCL matrix was previously proposed. In the present study, the potential of 3D fiber‐deposition technique to design morphologically controlled scaffolds consisting of PCL reinforced with PCL/TiO2 or PCL/ZrO2 hybrid fillers was demonstrated. Finite element analysis was initially carried out on 2D substrates to find a correlation between the previously obtained results from the small punch test and the Young's modulus of the materials, whilst mechanical and biological tests were suitably performed on rapid prototyped scaffolds to assess the effects of the inclusion of the hybrid fillers on the performances of the 3D porous structures. The role of the inclusion of the hybrid fillers in improving the compressive modulus (about 90 MPa) and the cell viability/proliferation was demonstrated. POLYM. COMPOS., 34:1413–1417, 2013. © 2013 Society of Plastics Engineers